Contemporary overview of metallo-Β-lactamases in pseudomonas aeruginosa: Epidemiology, detection methods and treatment challenges - Camargo, Carlos Henrique [UNESP]; Bruder-Nascimento, Ariane [UNESP]; Mondelli, Alessandro Lia [UNESP]; Montelli, Augusto Cezar [UNESP]; Sadatsune, Terue [UNESP] (My University, 2012)
Antimicrobial resistance poses a daunting challenge to treating bacterial infections. In Pseudomonas aeruginosa, an important opportunistic agent of nosocomial infection, antimicrobial resistance is well-pronounced and can be due to several intrinsic or acquired mechanisms. The therapeutic options to treat P. aeruginosa infection vary according to antimicrobial resistant patterns. Carbapenems, which had been longstanding last-line agents for treating P. aeruginosa infections, have become almost ineffective against this agent, mainly due to the emergence of carbapenemases. Metallo-ß-lactamases (MBL), enzymes from Bush and Jacoby's Group 3, are able to hydrolyze several substrates, such as carbapenems and cephalosporins. The genes encoding these enzymes are essentially located on mobile genetic elements that may be transferable to other strains or even distinct species. Considering their ubiquitous nature and potential to survive in hospital environments, early detection and implementation of contention barriers are desirable to prevent this bacterium from spreading throughout hospital settings and to prescribe a rational antibiotic regimen. Thus, fast and specific tests to detect MBL-producing P. aeruginosa are important both for bedside clinicians and hospital infection control committees. The purpose of this text is to provide an overview on the current status of the epidemiology, detection methods and treatment options for MBL-producing P. aeruginosa infections. © 2012 by Nova Science Publishers, Inc. All rights reserved.